NETRALITAS MEDIA MASSA ERA KINI - Kartinawati, Erwin (KOMUNITAS, 2013)
ThisÂ paperÂ isÂ toÂ highlightÂ theÂ reformationÂ ofÂ press freedomÂ inÂ termsÂ ofÂ theÂ principleÂ ofÂ media neutrality. Neutral, impartial or affiliated with stakeholders, and political power is one thing thatÂ is a principleÂ inÂ theÂ massÂ mediaÂ becauseÂ theÂ mediaÂ mustÂ maintainÂ itsÂ neutralityÂ asÂ aÂ functionÂ ofÂ social control and educator. If the period before the reform, freedom of the press overshadowed by âbredelâ or censorship, freedom apparently it isÂ still not fully considered in the present era. Freedom of the press is now just snatched away by its own internalmedia. If the first media workers have to struggle toÂ escapeÂ fromÂ theÂ politicalÂ repressionÂ ofÂ theÂ ruler,Â nowÂ mediaÂ workersÂ shouldÂ striveÂ toÂ avoid repression owners of capital with all the interest surrounding it, in order to realize the press that truly fair and responsible. Understanding and awareness of the owners of capital or management, at least for one word and one bow to actually enforce the primary purpose of journalism, not only for profit but noble responsibility to the community that is adream to realize a good Indonesian press.